Helium’s placement in the Periodic Table from a crystal structure viewpoint - Kurushkin, Mikhail (IUCrJ, 2020)
The present paper indicates that helium has more in common with the alkaline earths than is often considered. Not only does it share an analogous electron configuration but it also has an analogous crystal structure to that of beryllium and magnesium which is, in contrast, characteristic of the bulk material rather than of isolated atoms.